2016
DOI: 10.4183/aeb.2016.401
|View full text |Cite
|
Sign up to set email alerts
|

Mean Platelet Volume and Platelet Function Analysis in Acromegalic Patients Before and after Treatment

Abstract: Objective. Mean platelet volume (MPV) and platelet function analysis have been studied before in acromegaly, but the effect of treatment on both parameters has not been evaluated. We aimed to investigate MPV and platelet function analysis in acromegalic patients after sixmonths of treatment. Methods. Forty patients with active acromegaly and 36 healthy subjects were included in the study. Plasma glucose and lipids, fibrinogen, GH, IGF-1 levels, MPV and platelet function analysis were measured. All patients wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 25 publications
1
6
1
Order By: Relevance
“…Although, we failed to find any distinctions in MPV and MPV/PLT values between the three analyzed groups. These results are in contrast with those obtained by Arpaci et al, Demirpence et al, and Unübol et al, who noted significantly higher MPV value in acromegaly compared to healthy individuals [34,35,37].…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Although, we failed to find any distinctions in MPV and MPV/PLT values between the three analyzed groups. These results are in contrast with those obtained by Arpaci et al, Demirpence et al, and Unübol et al, who noted significantly higher MPV value in acromegaly compared to healthy individuals [34,35,37].…”
Section: Discussioncontrasting
confidence: 99%
“…Until now, there is only a single study concerning the relationship between SII and pituitary adenomas [32]. In accordance with previous data, we proved that the median platelet count was the lowest in patients with acromegaly compared with NFPAs and controls, but no statistical intergroup differences were observed [35]. It is well established that acromegaly is associated with increased morbidity and mortality due to cardiovascular diseases [5].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The treatment with SSA may thus increase MPV and be associated with greater risk of cardiovascular diseases. Demirpence et al demonstrated a significant decrease in MPV following surgery without adjuvant therapy [35]. MPV values remained unchanged in the active phase of the disease and in patients in remission who received SSA after surgery.…”
Section: Cushing's Diseasementioning
confidence: 97%
“…Research on MPV in acromegaly is inconclusive. Several studies have shown an increased MPV in acromegaly compared to healthy individuals [34][35][36], while another demonstrated no significant differences [37,38]. Surgical treatment with concomitant use of SSA was found to either increase or decrease MPV, whereas in patients treated only surgically no changes of MPV were noted [31,37].…”
Section: Cushing's Diseasementioning
confidence: 99%